Yeo Woon Taek v. New Nippon Steel Corporation. Issue 3 (July 2019) - Lee, Seokwoo; Lee, Seryon
Abstract : On October 30, 2018, the South Korean Supreme Court, in an 11–2 decision, upheld the judgment of the lower court, which ordered New Nippon Steel Corporation, a Japanese company, to provide KRW 100 million (approximately USD 84, 000) in compensation to each of the four plaintiffs, who were forced to work at Japanese steel mills during World War II. In an earlier 2012 decision, the Supreme Court remanded the case after holding that the claims were not precluded by the Agreement on the Settlement of Problems Concerning Property and Claims and the Economic Cooperation Between the Republic of Korea and Japan (Claims Agreement). The Supreme Court held that the Claims Agreement was not a result of negotiation about compensation for Japanese colonization, but rather was a political agreement the purpose of which was to resolve the financial and civil debt/credit relationship between Korea and Japan. On the final appeal, the Supreme Court concluded that plaintiffs' claims were directly related to the illegality of Japan's colonial rule over the Korean Peninsula and that the rights of the victims of forced labor to make a compensation claim did not fall within the scope of the Claims Agreement.